Characterization of a broad-spectrum antimicrobial peptide from Enterococcus mundtii active against bacteria associated with middle ear infections - Knoetze, Hendriette (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2006.